Timeliness and persistence of conservative earnings in an emerging market. Issue 3 (10th June 2020) - P., Afsheena; Santhakumar, Shijin
Abstract : Purpose: The asymmetric effect of conservatism on earnings and its other components serves as a contrivance to incorporate transparency and timeliness in financial reporting. This study aims to explore cash flow-return association, which provides insight into the accruals' contribution that traverses through conservatism-earnings persistence liaison and its associated effects on stock returns. Design/methodology/approach: The study used asymmetric timeliness (AT) model and two firm-year measures, namely, C-Score and conservatism ratio, to capture conservatism. The firm-year measures of conservatism, in addition to the AT measure, facilitate a better understanding of the persistence of reported earnings that branch out the study from the existing literature. Further, the study used panel regression analysis to evaluate the timeliness and persistence of earnings under the conservative approach with a sample of Indian corporate data from 2000 to 2017. Findings: The findings of the study reveal that conservative earnings are less persistent and the accruals recognize bad news timelier than good news. The unfavorable change in earnings shows a lower earnings response coefficient in contrast to favorable earnings variations. However, the appropriate loss recognition nature of conservative reporting has little or no influence on stock returns in an emerging market such as India. Research limitations/implications: Accounting conservatism is a captivating feature accounting information, especially pertinent to many decision-makers. Thus, the study has implications for the investors while evaluating the adverse and positive changes in accounting earnings; also, the results are helpful for the standard setters in ongoing debate related to accounting conservatism vs fair evaluation. The present study focuses exclusively on ex-post conservatism, while the ex post and ex ante conservatism are having a significant role in accounting practices. Future research on the differential effects of ex post and ex ante conservatism on accounting information in an emerging market, is worth promising. Originality/value: The study reveals the first Indian evidence on accounting conservatism and earnings persistence relationship, which would bring a different dimension to investors' perception in evaluating the characteristic variations of reported earnings. The findings add value to the accounting standard setters concerning the asymmetric verification as Indian Accounting standards are on the verge of convergence with International Financial Reporting Standards (IFRS).